STUDI NUMERIK KEKUATAN BAHAN PADA STRUKTUR CHASSIS DENGAN BEBAN STATIS DAN DINAMIS - Rahmatia; Lizda Johar Mawarani; Riyki Apriandi (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
The growth of microcars as an urban mobility solution demands an efficient yet strong and safe structural design. This study aims to analyze the structural performance of microcar chassis using a Finite Element Method (FEM)-based numerical simulation approach with ANSYS Workbench software. Evaluation was conducted on five types of materials-Aluminum 6061-T6, Aluminum 6082, Steel AISI 1018, Steel S355JR, and Carbon Fiber Reinforced Polymer (CFRP) Prepreg through static and dynamic analysis. Simulation results show that all materials have safety factor values above 1, with CFRP prepreg recording the highest value. Aluminum is considered the most optimal material for mass production because it is lightweight, strong enough, and economical. In the dynamic analysis, the entire structure showed a safe response to random vibration loads due to road surface irregularities, although there was potential for resonance at certain frequencies. Therefore, fatigue analysis is recommended for long-term evaluation. This study makes an important contribution to the design of lightweight, safe and sustainable microcar chassis.